2009
DOI: 10.1016/j.jhazmat.2008.05.141
|View full text |Cite
|
Sign up to set email alerts
|

In search of a reliable technique for the determination of the biological stability of the organic matter in the mechanical–biological treated waste

Abstract: The biological stability determines the extent to which readily biodegradable organic matter has decomposed. In this work, a massive estimation of indices suitable for the measurement of biological stability of the organic matter content in solid waste samples has been carried out. Samples from different stages in a Mechanical-Biological Treatment (MBT) plant treating municipal solid wastes (MSW) were selected as examples of different stages of organic matter stability in waste biological treatment.Aerobic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 33 publications
6
80
0
1
Order By: Relevance
“…VS and TOC showed to have roughly the same distribution in SBW I and in SBW IV (Fig. 3), proving the correlation between these two parameters (Bayard et al 2010) as they both are directly related to the organic carbon content (Barrena et al 2009). Differences between SBW I and SBW IV can be noticed since VS and TOC increased in classes A and B and decreased or kept roughly constant in classes C and D for SBW IV compared to SBW I.…”
Section: Organic Matter Contentmentioning
confidence: 58%
See 2 more Smart Citations
“…VS and TOC showed to have roughly the same distribution in SBW I and in SBW IV (Fig. 3), proving the correlation between these two parameters (Bayard et al 2010) as they both are directly related to the organic carbon content (Barrena et al 2009). Differences between SBW I and SBW IV can be noticed since VS and TOC increased in classes A and B and decreased or kept roughly constant in classes C and D for SBW IV compared to SBW I.…”
Section: Organic Matter Contentmentioning
confidence: 58%
“…Comparing UBW, SBW I and SBW IV, low reduction in VS and TOC content during biodegradation process can be observed (Leikam and Stegmann 1999;Lornage et al 2007;Barrena et al 2009;Bayard et al 2010). This is because VS and TOC take into account the overall organic matter, namely the nondegradable, slowly and readily degradable.…”
Section: Organic Matter Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, to address increasing energy consumption and the steady depletion of fossil fuel reserve, many investigations have been conducted to develop alternative and renewable energy resources using biomass and waste [1,2]. Because rapid urbanization is occurring almost everywhere in the world, substantially increasing municipal solid waste (MSW), which is of great global concern.…”
Section: Introductionmentioning
confidence: 99%
“…This indicator does not, however, necessarily reflect the nature of the material and its potential for biodegradability (Ponsa et al, 2010). Among other stability indicators used in the studies of composts or biological wastes, respirometric activity is the most typically used indicator of microbial activity (Barrena et al, 2009). Schievano et al (2008) demonstrated that an oxygen uptake rate (OUR) assay in combination with volatile solids data can be useful to evaluate the performance of the anaerobic digestion process.…”
Section: Introductionmentioning
confidence: 99%